The mechanism of trans-δ-viniferin inhibiting the proliferation of lung cancer cells A549 by targeting the mitochondria - Ruochun Yin; Ruochun Yin; Yiling Zhang; Liping Su; Dongdong Chen; Shidi Lou; Xuecai Luo; Lin Wang; Lin Wang; Rupei Tang; Liang Zhang; Xiaohe Tian (Frontiers Media S.A., 2023)
Trans-δ-viniferin (TVN), as a natural extract, is a resveratrol dimer with attractive biological activities, particularly its anti-tumor character. However, the mechanism of TVN interfering with cancerous proliferation has not been fully understood. Herein in this study, we found that TVN could trigger cancerous mitochondrial membrane potential (ΔΨm) reduction, with intracellular reactive oxidative species (ROS) level increasing, leading to apoptosis, which makes TVN a promising candidate for lung cancer cells A549 treatment. Therefore, this study provides TVN as an option to meet the demand for higher antitumor availability with lower biotoxicity and other clinical applications.